String Processing and Information Retrieval 20th International Symposium, SPIRE 2013, Jerusalem, Israel, October 7-9, 2013, Proceedings - Kurland, Oren.; Lewenstein, Moshe; Porat, Ely.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 20th International Symposium on String Processing and Information Retrieval, SPIRE 2013, held in Jerusalem, Israel, in October 2013. The 18 full papers, 10 short papers were carefully reviewed and selected from 60 submissions. The program also featured 4 keynote speeches. The following topics are covered: fundamentals algorithms in string processing and information retrieval; SP and IR techniques as applied to areas such as computational biology, DNA sequencing, and Web mining.
Consolidating and Exploring information via Textual Inference -- Pattern Discovery and Listing in Graphs -- Efficient Approximation of Edit Distance -- Nowcasting with Google Trends -- Space-efficient Construction of the Burrows-Wheeler Transform -- Using Mutual Inuence to Improve Recommendations -- Position-Restricted Substring Searching Over Small Alphabets -- Simulation Study of Multi-threading in Web Search Engine Processors -- Query Processing in Highly-Loaded Search Engines -- Indexes for Jumbled Pattern Matching in Strings, Trees and Graphs -- Adaptive Data Structures for Permutations and Binary Relations -- Document Listing on Versioned Documents -- Order-Preserving Incomplete Suffix Trees and Order-Preserving Indexes -- Compact Querieable Representations of Raster Data -- Top-k Color Queries On Tree Paths -- A Lempel-Ziv Compressed Structure for Document Listing -- Minimal Discriminating Words Problem Revisited -- Adding Compression and Blended Search to a Compact Two-Level Suffix Array -- You are what you eat: learning user tastes for rating prediction -- Discovering dense subgraphs in parallel for compressing Web and Social networks -- Faster Lyndon factorization algorithms for SLP and LZ78 compressed text -- Lossless compression of rotated maskless lithography images -- Learning URL Normalization Rules using Multiple Alignment of Sequences -- On Two-Dimensional Lyndon Words -- Fully-Online Grammar Compression -- Solving Graph Isomorphism using Parameterized Matching -- Suffix Array of Alignment: A Practical Index for Similar Data -- Faster Top-k Document Retrieval in Optimal Space -- Faster Range LCP Queries -- Learning to Schedule Webpage Updates Using Genetic Programming -- Accurate Profiling of Microbial Communities from Massively Parallel Sequencing using Convex Optimization -- Distributed Query Processing on Compressed Graphs using K2-Trees.
Keywords: Computer science; Computer software; Data mining; Information storage and retrieval systems; Optical pattern recognition; Computer Science; Information Storage and Retrieval; Pattern Recognition; Algorithm Analysis and Problem Complexity; Data Mining and Knowledge Discovery